Age at first menstruation and clinical breast cancer screening utilization: insights from the 2021 Côte d'Ivoire demographic and health survey - Joshua Okyere; Castro Ayebeng; Sylvia Ahinee Adjedu; Kwamena Sekyi Dickson (Reproductive Health)
Abstract Background There is a strong evidence showing that women who start menstruation early are at a greater risk of developing breast cancer. Recognizing that women will seek breast cancer screening when they have a high perceived risk, we hypothesized that women who experienced early menarche will be more likely to utilize clinical breast examination (CBE). Hence, we aimed to investigate the association between age at first menstruation and women’s utilization of CBE in Côte d'Ivoire. Methods We used data from the 2021 Côte d'Ivoire demographic and health survey. A sample of 14,685 women was used for the analysis. A descriptive analysis, as well as bivariate and multivariate logistic regression models were computed in STATA version 18. Adjusted odds ratio (AOR) and a 95% confidence interval was used to present the result. Results CBE utilization was 17.4%. Women who had their first menstruation before attaining 15 years were significantly less likely to utilize CBE services [AOR = 0.89; 95% CI 0.81–0.99]. A significantly higher utilization of CBE was found among those with primary [AOR = 1.48, 95% CI 1.29–1.70], secondary [AOR = 2.96, 95% CI 2.59–3.38], and higher education [AOR = 4.35, 95% CI 3.50–5.40] compared to those with no formal education. Increasing likelihood of CBE utilization was observed as age increased. Rural residence was associated with lower odds of CBE utilization (AOR = 0.84, 95% CI 0.74–0.95]. Increasing wealth status was associated with higher odds of CBE utilization with those in the richest households having the highest odds compared to women in the poorest household [AOR = 2.11, 95% CI 1.69–2.64]. Conclusion Utilization of CBE is low among women of reproductive age in Côte d'Ivoire. We conclude that even though existing literature has established early age at first menstruation as a strong risk factor for breast cancer, CBE utilization is significantly low among those who had early menarche. Going forward, it is necessary for Côte d'Ivoire’s health Ministry to intensify breast cancer awareness in the country. Such awareness campaigns must emphasize age at menarche as a risk factor so as to motivate women with a history of early menstruation to utilize CBE.